The Moderating Role of Organizational Citizenship Behavior Toward Environment on Relationship Between Green Supply Chain Management Practices and Sustainable Performance - Azam, Tamoor; Malik, Saqib Yaqoob; Ren, Diandian; Yuan, Wenrong; Mughal, Yasir Hayat; Ullah, Irfan; Fiaz, Muhammad; Riaz, Sidra (Frontiers in Psychology, 2022)
This research study has examined the moderating part of “organizational citizenship behaviour for the environment” (OCBE) on the corresponding relation of“green supply chain management” (GSCM) practices and sustainable performance from the perspective of “natural resource-based view” (NRBV).The survey method was used while data was collected from manufacturing firms; the analysis used 151 responses. For statistical analysis, “SmartPLS partial least square, structural equation modelling” PLS-SEM was used. It is a 2nd generation statistical tool. It usually runs small and non-normal data sets. From the findings, it was evident that in the measurement model, concurrent and discriminant validities were established. In the second stage structural model was developed for hypotheses testing. It was found that sustainable performance was affirmatively associated with proposed GSCM practices, excluding environmental management (EE). Whereas OCBE being a moderator has affirmative and influential impacts concerning GSCM operations and sustainability functions of firms. However, OCBE did not play the role of moderator for the correlation between internal environmental management &EE and sustainable performance. The present study is significant for managers and policymakers for the attainment of competitive advantage, enhance OCBE and sustainable performance. Further, this research study is the first empirical study that has used OCBE as a moderator through the lens of NRBV.